KONSEP LOYALITAS PELANGGAN: PERSPEKTIF BEHAVIORAL DAN PERSPEKTIF ATTITUDINAL - Ramadania, . (Fakultas Ekonomi dan Bisnis, UNTAN, 2010)
ABSTRACT The aim of this article is to discuss customer’s loyalty as a complex dimension in consumer behavior theory. Customer’s loyalty can stimulate brand loyalty describing a condition in which consumers have postitive attitude toward a brand, have commitment to it, and have intention to continue buying it in the future. Brand loyalty can be analyzed by two perspectives : behavioral persepective and attitudinal persepective. These are reflected in consumer’s actual buying behavior and consumer’s psychological commitment. Understanding these two perspectives are very important for marketers in devising a competitive marketing strategy. Kata Kunci: Loyalitas pelanggan, Perspektif Behavioral Dan Perspektif Attitudinal